Magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect cell proliferation stimulation function and preparation method of magnesium phosphate bone cement

By ion doping and constructing heterojunction-modified sodium tantalate nanomaterial combined with magnesium phosphate bone cement, modified magnesium phosphate bone cement with acoustic dynamic antibacterial and piezoelectric effects was prepared, which solved the problem of low osteogenic and antibacterial properties in the prior art, and achieved significant antibacterial effects and the effect of promoting cell proliferation.

CN119548666APending Publication Date: 2025-03-04XIN HUA HOSPITAL AFFILIATED TO SHANGHAI JIAO TONG UNIV SCHOOL OF MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411466555.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

When used in bone defect repair, existing magnesium phosphate bone cement has low osteogenic performance and antibacterial properties and cannot meet clinical needs.

Method used

Modified magnesium phosphate bone cement with acoustic dynamic antibacterial and piezoelectric effects were prepared by ionic doping and constructing heterojunction modified sodium tantalate (NTO) nanomaterials and composited with magnesium phosphate bone cement (MPC).

Benefits of technology

The modified magnesium phosphate bone cement significantly inhibited the growth of E. coli and S. aureus under ultrasonic irradiation, and the antibacterial rate reached 93.45% and 90.89%; at the same time, the proliferation of osteoblasts was significantly promoted in vitro, and the cell proliferation rate was 46.2% higher than that of pure MPC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548666A_ABST
    Figure CN119548666A_ABST
Patent Text Reader

Abstract

The invention discloses magnesium phosphate bone cement with sonodynamic antibiosis / piezoelectric effect for stimulating cell proliferation. The magnesium phosphate bone cement is prepared from CaHPO4, NaH2PO4, MgO powder, hydroxyapatite and a heterojunction containing BOS. According to the invention, NTO is modified through ion doping and heterojunction construction, a nano material with both sonodynamic performance and piezoelectric performance is prepared, the nano material and MPC are compounded, and the modified magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect stimulated cell proliferation is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials, and in particular, relates to a magnesium phosphate bone cement having sonodynamic antibacterial / piezoelectric effect for stimulating cell proliferation and a preparation method thereof. Background Art

[0002] Bone defects caused by trauma, infection, etc. are a common orthopedic clinical lesion, and artificial bone transplantation is an effective method of bone repair. In recent years, magnesium phosphate cement (MPC) has been favored as an artificial bone substitute material because its chemical composition is close to the mineral composition of bone tissue, has good biocompatibility, and has a certain ability to promote osteoblast proliferation and differentiation. In addition, magnesium phosphate cement also has certain adhesion, plasticity and support, and can adapt to different types of bone defects, which is very advantageous in clinical applications.

[0003] The osteogenic and antibacterial properties of MPC due to the presence of magnesium ions have been verified, but the activity is low and cannot be directly applied to bone defect repair. Therefore, how to improve the osteogenic and antibacterial properties of MPC has received widespread attention. Sonodynamic therapy (SDT) has been widely used in antibacterial treatment. It kills pathogenic bacteria by generating reactive oxygen species (ROS) through ultrasound (US) irradiation of sonosensitizers. Sonosensitizers are considered to be the core of SDT. Bones have a natural piezoelectric effect, and their electrical properties are closely related to their remodeling and regeneration. Piezoelectric materials can promote bone regeneration by providing appropriate electrical stimulation to cells under stress.

[0004] Sodium tantalate (NaTaO 3 , NTO) is a piezoelectric semiconductor material with high electron and hole separation efficiency and ROS generation efficiency under UV-visible light irradiation, and is a potential sonosensitizer. In addition, NTO not only has a piezoelectric effect, but also has excellent biocompatibility and osteogenic activity. However, pure NTO has problems such as poor sonodynamic properties and limited piezoelectric properties. Ion doping and heterostructure construction have been proven to be effective strategies to improve the sonodynamic properties of materials. The introduction of oxygen vacancies through ion doping can reduce the band gap width of the sonosensitizer, making it easier to be activated by US. At the same time, ion doping can induce lattice distortion and improve the piezoelectric properties of piezoelectric materials; Bi 2 O 2 Se(BOS) has excellent charge migration / transport capabilities. When constructing heterojunctions with semiconductors, it can act as an electron transfer carrier to promote the separation of electron and hole pairs, thereby improving the sonodynamic performance. In addition, BOS has excellent electrical conductivity and is expected to improve the charge transport inside piezoelectric materials and enhance piezoelectric performance. Summary of the invention

[0005] The purpose of the present invention is to provide a magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation.

[0006] Another object of the present invention is to provide a method for preparing the magnesium phosphate bone cement having the sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] The first aspect of the present invention provides a magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation, which is composed of CaHPO 4 、NaH 2 PO 4 , MgO powder, hydroxyapatite, containing BOS (Bi 2 O 2 Se), CaHPO 4 、NaH 2 PO 4 The molar ratio of hydroxyapatite to MgO is 1 to 4:1 to 4:1 (preferably 2:2:1), and the mass of hydroxyapatite accounts for 1:1 of CaHPO 4 、NaH 2 PO 4 The total mass percentage of MgO is 5-20wt% (preferably 10wt%), containing BOS (Bi 2 O 2 The mass of the heterojunction of CaHPO 4 、NaH 2 PO 4 , MgO, hydroxyapatite and BOS(Bi 2 O 2 The mass percentage of the total mass of the heterojunction of Se) is 5-50wt% (preferably 10wt%, 20wt%, 40wt%).

[0009] The BOS (Bi 2 O 2 The heterojunction of Se) is composed of Bi / N co-doped NaTaO with a mass ratio of 1-100:1-50:1:0.1-10:1-500 (preferably 20.4:7.7:1:2.2:226, 20.4:2.6:1:0.7:226, 20.4:12.9:1:3.5:226) 3 (NTO(Bi / N)) nanomaterials, bismuth nitrate Bi(NO 3 ) 3 、N 2 H 4 ·H 2 O、SeO 2 , made of sodium hydroxide.

[0010] The Bi / N co-doped NaTaO 3 The (NTO(Bi / N)) nanomaterial is composed of tantalum pentoxide Ta in a molar ratio of 1:0.005-0.04:1-5:1-100 (preferably 1:0.02:1.36:14.3, 1:0.02:2.71:14.3, 1:0.02:4.07:14.3) 2 O 5 , Bi(NO 3 ) 3 , ammonia water and sodium hydroxide.

[0011] The second aspect of the present invention provides a method for preparing the magnesium phosphate bone cement having sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation, comprising the following steps:

[0012] CaHPO in a molar ratio of 1 to 4:1 to 4:1 (preferably 2:2:1) 4 、NaH 2 PO 4 Mix with MgO powder, add hydroxyapatite (HA) and mix evenly. The mass of hydroxyapatite accounts for 1.3% of CaHPO. 4 、NaH 2 PO 4 The total weight percentage of MgO is 5 to 20 wt% (preferably 10 wt%), and the obtained mixed powder is mixed with BOS (Bi 2 O 2 Se) heterojunction is evenly mixed, containing BOS (Bi 2 O 2 The mass of the heterojunction of CaHPO 4 、NaH 2 PO 4 , MgO, hydroxyapatite and BOS(Bi 2 O 2 The mass percentage of the total mass of the heterojunction of Se) is 5-50wt% (preferably 10wt%, 20wt%, 40wt%), deionized water is added to make the liquid-to-solid ratio 170-210μL / g (preferably 170μL / g, 190μL / g, 210μL / g), and the mixture is fully blended and filled into a mold, formed, and cured to obtain the magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation.

[0013] The curing conditions are as follows: the sample is placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 1 to 72 hours (preferably 72 hours).

[0014] The BOS (Bi 2 O 2The preparation method of the heterojunction of Se) comprises the following steps:

[0015] The concentration of N is 20-50 wt% (preferably 40 wt%). 2 H 4 ·H 2 O and SeO 2 Dissolve in a 5-15M (preferably 12.5M) NaOH aqueous solution, N 2 H 4 ·H 2 The volume ratio of O and NaOH aqueous solution is 0.1-1:1 (preferably 0.28:1), and stirring is continued for 20-60 min (preferably 40 min) to obtain solution A;

[0016] Bi / N co-doped NaTaO 3 (NTO(Bi / N)) nanomaterials are dispersed in Bi(NO 3 ) 3 , in a NaOH aqueous solution with a concentration of 0.1 to 1 M (preferably 0.5 M), stirring for 20 to 60 min (preferably 40 min) to obtain a solution B;

[0017] Bi / N co-doped NaTaO 3 (NTO(Bi / N)) nanomaterials, bismuth nitrate Bi(NO 3 ) 3 、N 2 H 4 ·H 2 O、SeO 2 , the mass ratio of sodium hydroxide is 1-100:1-50:1:0.1-10:1-500 (preferably 20.4:7.7:1:2.2:226, 20.4:2.6:1:0.7:226, 20.4:12.9:1:3.5:226);

[0018] Solution A is added dropwise to solution B and stirred for 0.5 to 2 hours (preferably 1 hour), the volume ratio of solution A to solution B is 1.1 to 1.5:1 (preferably 1.26:1, 1.3:1, 1.28:1), and the temperature is 150 to 300° C. (preferably 200° C.) for hydrothermal reaction for 0.5 to 24 hours (preferably 24 hours), and the product is washed and dried after the reaction to obtain the BOS (Bi 2 O 2 Se) heterojunction.

[0019] The Bi / N co-doped NaTaO 3 The preparation method of (NTO(Bi / N)) nanomaterial comprises the following steps:

[0020] Will Ta2 O 5 Dispersed in a NaOH solution with a concentration of 0.5 to 3 M (preferably 2 M), Ta 2 O 5 The molar ratio of Bi(NO 3 ) 3 and ammonia as Bi and N sources were added to the above solution, Ta 2 O 5 , Bi(NO 3 ) 3 The molar ratio of the Bi / N co-doped NaTaO is 1:0.005-0.04:1-5 (preferably 1:0.02:1.36, 1:0.02:2.71, 1:0.02:4.07), stirred in a sealed state for 0.5-2h (preferably 1h), reacted at a temperature of 140-200°C (preferably 160°C) for 0.5-24h (preferably 12h), washed with deionized water, dried, and annealed to obtain the Bi / N co-doped NaTaO 3 (NTO(Bi / N)) nanomaterials.

[0021] The drying conditions are as follows: drying at a temperature of 50 to 80° C. (preferably 60° C.) for 0.5 to 24 h (preferably 12 h).

[0022] The annealing conditions are: annealing at a temperature of 350 to 500° C. (preferably 400° C.) for 0.5 to 2 h (preferably 1 h).

[0023] The third aspect of the present invention provides a use of the magnesium phosphate bone cement having sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation in the preparation of a bone repair scaffold.

[0024] The fourth aspect of the present invention provides a use of the magnesium phosphate bone cement having sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation in the preparation of bone repair materials or bone transplant materials.

[0025] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:

[0026] The present invention prepares a nanomaterial with both sonodynamic and piezoelectric properties by ion doping and constructing a heterojunction modified NTO, and composites the nanomaterial with MPC to prepare a modified magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation. The MPC / BOS@NTO (Bi / N) composite bone cement provided by the present invention shows a significant inhibitory effect on E coli and Saureus, with the inhibition rates reaching 93.45% and 90.89% respectively, indicating that it has an excellent sonodynamic antibacterial effect; at the same time, the MPC / BOS@NTO (Bi / N) composite bone cement promotes the proliferation of rBMSCs in vitro, and the cell proliferation rate is 46.2% higher than that of MPC, indicating that it has an excellent piezoelectric effect to stimulate cell proliferation. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the acoustic dynamic performance test results of the sample under US irradiation.

[0028] Figure 2 It is a schematic diagram of the SEM image and EDS spectrum of the sample.

[0029] Figure 3 Schematic diagram of XRD spectra of NTO, NTO(Bi / N), BOS and BOS@NTO(Bi / N).

[0030] Figure 4 It is a schematic diagram of the Tauc curves and XPS-VB spectra of NTO, NTO(Bi / N) and BOS.

[0031] Figure 5 Schematic diagram of the electrochemical impedance spectra of NTO, NTO(Bi / N), BOS and BOS@NTO(Bi / N) and its curves under ultrasonic irradiation.

[0032] Figure 6 Schematic diagram of (a) amplitude image, (b) phase image, (c) amplitude butterfly loop and (d) hysteresis loop of BOS@NTO(Bi / N).

[0033] Figure 7 Schematic diagram of the mechanism of ROS generation by BOS@NTO(Bi / N) under US irradiation.

[0034] Figure 8 It is a schematic diagram of the acoustic dynamic performance test results of the sample.

[0035] Fig. 9 It is a schematic diagram of the piezoelectric performance test results of the sample.

[0036] Fig.10 It is a colony image of the antimicrobial plate count and a schematic diagram of the bacterial survival rate results.

[0037] Fig.11 This is a schematic diagram of the cytotoxicity and cell proliferation results of the samples. DETAILED DESCRIPTION

[0038] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0039] Example 1

[0040] Bi / N co-doped NaTaO prepared by hydrothermal method 3 (NTO(Bi / N)) nanomaterial, the preparation method comprises the following steps:

[0041] Tantalum pentoxide Ta 2 O 5 (7.00mmol, 3.087g) was dispersed in 50mL of 2M NaOH solution and bismuth nitrate Bi(NO 3 ) 3 (0.14mmol, 0.055g) was added to the above solution as a Bi source. Stirred for 1h in a sealed state, the mixture was transferred to an autoclave, placed in an oven at 160℃ for reaction for 12h, and washed three times with 50mL of deionized water. Dry at 60℃ for 12h, and annealed at 400℃ for 1h to eliminate crystal water to obtain 2mol% Bi-doped NTO.

[0042] The preparation method of 1mol% Bi-doped NTO comprises the following steps:

[0043] Will Ta 2 O 5 (7.00mmol, 3.087g) was dispersed in 50mL of 2M NaOH solution and Bi(NO 3 ) 3 (0.07mmol, 0.028g) was added to the above solution as a Bi source. Stirred for 1h in a sealed state, the mixture was transferred to an autoclave, placed in an oven at 160°C for reaction for 12h, and washed three times with 50mL of deionized water. Dry at 60°C for 12h, and annealed at 400°C for 1h to eliminate crystal water to obtain 1mol% Bi-doped NTO.

[0044] The preparation method of 3mol% Bi-doped NTO comprises the following steps:

[0045] Will Ta 2 O 5(7.00mmol, 3.087g) was dispersed in 50mL of 2M NaOH solution and Bi(NO 3 ) 3 (0.21mmol, 0.083g) was added to the above solution as a Bi source. Stirred for 1h in a sealed state, the mixture was transferred to an autoclave, placed in an oven at 160℃ for reaction for 12h, and washed three times with 50mL of deionized water. Dry at 60℃ for 12h, and annealed at 400℃ for 1h to eliminate crystal water to obtain 3mol% Bi-doped NTO.

[0046] The Bi doping amount was fixed at 2 mol%, and 370 μl of ammonia water was added as a N source to prepare Bi / N co-doped NTO:

[0047] Will Ta 2 O 5 (7.00mmol, 3.087g) was dispersed in 50mL of 2M NaOH solution and Bi(NO 3 ) 3 (0.14mmol, 0.055g) and 370μl ammonia water (9.5mmol, 0.333g) were added to the above solution as Bi source and N source. Stirred for 1h in a sealed state, the mixture was transferred to an autoclave, placed in an oven at a temperature of 160℃ for reaction for 12h, and washed three times with 50mL deionized water. Drying at a temperature of 60℃ for 12h, and annealing at a temperature of 400℃ for 1h to eliminate crystal water, Bi / N co-doped NTO, i.e. NTO (B 2 N 1 ).

[0048] The Bi doping amount was fixed at 2 mol %, and 740 μl of ammonia water was added as a N source to prepare Bi / N co-doped NTO.

[0049] Will Ta 2 O 5 (7.00mmol, 3.087g) was dispersed in 50mL of 2M NaOH solution and Bi(NO 3 ) 3 (0.14mmol, 0.055g) and 740μl ammonia water (19.0mmol, 0.667g) were added to the above solution as Bi source and N source. Stirred for 1h in a sealed state, the mixture was transferred to an autoclave, placed in an oven at a temperature of 160℃ for reaction for 12h, and washed three times with 50mL of deionized water. Dry at a temperature of 60℃ for 12h, and annealed at a temperature of 400℃ for 1h to eliminate crystal water to obtain Bi / N co-doped NTO, i.e. NTO(B / N).

[0050] The Bi doping amount was fixed at 2 mol %, and 1110 μl of ammonia water was added as a N source to prepare Bi / N co-doped NTO.

[0051] Will Ta 2 O 5 (7.00mmol, 3.087g) was dispersed in 50mL of 2M NaOH solution and Bi(NO 3 ) 3 (0.14mmol, 0.055g) and 1110μl ammonia water (28.5mmol, 0.999g) were added to the above solution as Bi source and N source. Stirred for 1h in a sealed state, the mixture was transferred to an autoclave, placed in an oven at a temperature of 160℃ for reaction for 12h, and washed three times with 50mL of deionized water. Drying at a temperature of 60℃ for 12h, and annealing at a temperature of 400℃ for 1h to eliminate crystal water, Bi / N co-doped NTO, i.e. NTO (B 2 N 3 ).

[0052] The sample groups are shown in Table 1:

[0053] Table 1 Bi / N co-doped NTO sample grouping

[0054]

[0055]

[0056] Preparation of BOS@NTO(Bi / N)

[0057] In-situ generation of Bi on NTO (Bi / N) surface via hydrothermal method 2 O 2 Se(BOS).

[0058] 2.80 mL of 40 wt% N 2 H 4 ·H 2 O (0.45 mmol, 0.023 g) and SeO 2 (0.45 mmol, 0.05 g) was dissolved in 10 mL of 12.5 M NaOH aqueous solution and stirred continuously for 40 min to obtain 13.3 mL of solution A.

[0059] The NTO (Bi / N) (0.47 g) prepared in Example 1 was dispersed in 10 mL of Bi(NO 3 ) 3 (0.45 mmol, 0.178 g) and 0.5 M NaOH aqueous solution were stirred for 40 min to obtain 10.4 mL of solution B.

[0060] 13.3 mL of solution A was added dropwise to 10.4 mL of solution B and stirred for 1 h. The solution was transferred to an autoclave and subjected to a hydrothermal reaction at 200 °C for 24 h. After the reaction, the product was washed and dried to obtain 0.251 g of a 30 wt% Bi 2 O 2 Heterojunction of Se(BOS), namely BOS@NTO(Bi / N).

[0061] Bi 2 O 2 The preparation method of Se(BOS) comprises the following steps:

[0062] 2.80 mL of 40 wt% N 2 H 4 ·H 2 O (0.45 mmol, 0.023 g) and SeO 2 (0.45 mmol, 0.05 g) was dissolved in 10 mL of 12.5 M NaOH aqueous solution and stirred continuously for 40 min to obtain 13.3 mL of solution A.

[0063] Take 10 mL of Bi(NO 3 ) 3 (0.45 mmol, 0.178 g) and a 0.5 M NaOH aqueous solution were used as solution B.

[0064] 13.3 mL of solution A was added dropwise to 10 mL of solution B and stirred for 1 h. The solution was transferred to an autoclave and subjected to a hydrothermal reaction at 200 °C for 24 h. After the reaction, the product was washed and dried to obtain 0.074 g of Bi 2 O 2 Se(BOS).

[0065] Contains 10wt%Bi 2 O 2 The method for preparing the heterojunction of Se(BOS) comprises the following steps:

[0066] 2.80 mL of 40 wt% N 2 H 4 ·H 2 O (0.45 mmol, 0.023 g) and SeO 2 (0.15 mmol, 0.016 g) was dissolved in 10 mL of 12.5 M NaOH aqueous solution and stirred continuously for 40 min to obtain 13.1 mL of solution A.

[0067] The NTO (Bi / N) (0.47 g) prepared in Example 1 was dispersed in 10 mL of Bi(NO 3 ) 3 (0.15 mmol, 0.059 g) and 0.5 M NaOH aqueous solution were stirred for 40 min to obtain 10.4 mL of solution B.

[0068] 13.1 mL of solution A was added dropwise to 10.4 mL of solution B and stirred for 1 h. The solution was transferred to an autoclave and subjected to a hydrothermal reaction at 200 °C for 24 h. After the reaction, the product was washed and dried to obtain 0.196 g of a 10 wt% Bi 2 O 2 Heterojunction of Se(BOS).

[0069] Contains 50wt% Bi 2 O 2 The method for preparing the heterojunction of Se(BOS) comprises the following steps:

[0070] 2.80 mL of 40 wt% N 2 H 4 ·H 2 O (0.45 mmol, 0.023 g) and SeO 2 (0.75 mmol, 0.08 g) was dissolved in 10 mL of 12.5 M NaOH aqueous solution and stirred continuously for 40 min to obtain 13.6 mL of solution A.

[0071] The NTO (Bi / N) (0.47 g) prepared in Example 1 was dispersed in 10 mL of Bi(NO 3 ) 3 (0.75 mmol, 0.296 g) and 0.5 M NaOH aqueous solution were stirred for 40 min to obtain 10.4 mL of solution B.

[0072] 13.6 mL of solution A was added dropwise to 10.4 mL of solution B and stirred for 1 h. The solution was transferred to an autoclave and subjected to a hydrothermal reaction at 200 °C for 24 h. After the reaction, the product was washed and dried to obtain 0.298 g of a 50 wt% Bi 2 O 2 Heterojunction of Se(BOS).

[0073] The sample groups are shown in Table 2:

[0074] Table 2 Grouping of samples for heterojunction constructed by BOS and NTO (Bi / N)

[0075]

[0076] Acoustic dynamic performance test of samples:

[0077] Under US irradiation, the sonodynamic properties of the samples were detected using rhodamine B (Rh B) indicator (·O 2 - 5 mg of sample powder was dispersed in 10 ml of indicator rhodamine B solution and the solution was heated under light-proof conditions using US (1.5 W / cm 2 , 1MHz) irradiation for 10min, centrifugation and removal of the supernatant, the absorption spectrum of which was measured by UV-visible spectrophotometer. The concentration of Rh B used was 10mg / L.

[0078] The results are as follows Figure 1 As shown, Figure 1 is a schematic diagram of the acoustic dynamic performance test results of the sample under US irradiation, where a is the evaluation of Bi-doped NaTaO by Rh B degradation 3 Schematic diagram of the results of the ROS generation ability of nanomaterials, (b) the degradation of Bi / N co-doped NaTaO by Rh B 3 c is a schematic diagram of the results of the ability of nanomaterials to generate ROS, c is a schematic diagram of the results of evaluating the ability of heterojunctions containing BOS to generate ROS using Rh B degradation, and d is a schematic diagram of the relationship between the ability of BOS@NTO (Bi / N) to generate ROS and the US irradiation time. Figure 1 As shown in Figure a, the acoustic dynamic performance of the material increases with the increase of Bi doping content, but when the Bi doping content is too high, its acoustic dynamic performance decreases. 2 )Optimal acoustic dynamic performance. Figure 1 Figure b shows that when the Bi doping content is fixed, the acoustic dynamic performance of the nanomaterial increases with the increase of the N doping content. However, if the N doping content is too high, its acoustic dynamic performance decreases. Among them, NTO (Bi / N) has the best acoustic dynamic performance. Figure 1 Figure c shows that as the BOS content increases, the acoustic dynamic performance of the heterojunction improves, but when the BOS content is too high, its acoustic dynamic performance decreases. Among them, the heterojunction containing 30wt% BOS, namely BOS@NTO (Bi / N), has the best acoustic dynamic performance. Figure 1 Figure d shows that the degradation efficiency of Rh B by BOS@NTO(Bi / N) increases with the extension of US time.

[0079] Morphology and structure characterization:

[0080] SEM analysis: The microstructure and particle size of NTO, BOS, NTO(Bi / N) and BOS@NTO(Bi / N) were observed using scanning electron microscopy.

[0081] EDS analysis: Energy dispersive spectrometer was used to analyze the elemental composition of NTO, BOS, NTO(Bi / N) and BOS@NTO(Bi / N).

[0082] The results are as follows Figure 2 As shown, Figure 2 Schematic diagram of the SEM image and EDS spectrum of the samples, wherein a is a schematic diagram of the SEM image of NTO, b is a schematic diagram of the SEM image of NTO(Bi / N), c is a schematic diagram of the SEM image of BOS, d is a schematic diagram of the SEM image of BOS@NTO(Bi / N), e is a schematic diagram of the SEM image of NTO at a high magnification, f is a schematic diagram of the SEM image of NTO(Bi / N), g is a schematic diagram of the SEM image of BOS at a high magnification, h is a schematic diagram of the SEM image of BOS@NTO(Bi / N), i is a schematic diagram of the EDS spectrum of NTO, j is a schematic diagram of the EDS image of NTO(Bi / N), k is a schematic diagram of the EDS image of BOS, and l is a schematic diagram of the EDS image of BOS@NTO(Bi / N).

[0083] SEM images show that NTO has a regular cubic crystal morphology with a particle size of 400-500nm ( Figure 2 Compared with NTO, the particle size of NTO (Bi / N) is 200-300 nm, which is significantly smaller ( Figure 2 This is because Bi 3+ In replacing Na + The charge imbalance induced by the BOS will hinder the growth of NTO. BOS is an irregular block, which is composed of extremely thin layer structures with a width of 1.3μm ( Figure 2 c and g); Figure 2 Figures d and h show that BOS with a particle size of 50 nm is evenly distributed on the heterojunction surface. The size and morphology of pure BOS and BOS@NTO(Bi / N) are significantly different. The size of pure BOS is 1.3 μm, and the size of BOS@NTO(Bi / N) is 50 nm. The morphology of pure BOS is a block formed by stacking layers, while the morphology of BOS@NTO(Bi / N) is spherical particles. This may be because NTO(Bi / N) affects the crystallization of BOS. The EDS spectrum shows that NTO only has uniformly distributed Na, Ta, and O characteristic elements ( Figure 2 As shown in (i), BOS only has uniformly distributed Bi, O, and Se characteristic elements ( Figure 2 In addition, Na, Ta, O, Bi and N characteristic elements are evenly distributed NTO (Bi / N) ( Figure 2 j) and BOS@NTO(Bi / N)( Figure 2The surface of BOS@NTO (Bi / N) is also uniformly distributed with Se characteristic elements originating from BOS.

[0084] XRD analysis: The crystal structures of NTO, BOS, NTO(Bi / N) and BOS@NTO(Bi / N) were characterized by X-ray diffraction.

[0085] The results are as follows Figure 3 As shown, Figure 3 Figure 1 is a schematic diagram of the XRD spectra of NTO, NTO(Bi / N), BOS and BOS@NTO(Bi / N). The XRD spectra show that NTO, NTO(Bi / N) and BOS@NTO(Bi / N) all have the characteristic peaks of perovskite-type NTO (2θ=22.84, 32.46, 40.12, 46.56, 52.42, 57.94, 67.96, 72.82 and 77.40°); for BOS, its characteristic peaks are consistent with the literature (GaoY, Niu X, Pan L, et al. Effects of MoS 2 addtion on the thermoelectric properties of Bi 2 O 2 Se[J].Solid State Sciences, 2023, 138:107147.) reported (2θ=24.24, 28.64, 31.48, 32.54, 44.96, 46.7, 56.20 and 57.98°), and Bi also appeared in the spectrum. 2 Se 3 The characteristic peak (39.78°) and Bi 2 O 3 This is because oxygen and selenium have the same outermost electronic structure, and lattice atoms replace each other during the crystallization of BOS. In addition, BOS@NTO(Bi / N) has the characteristic peaks of NTO(Bi / N) and BOS.

[0086] Analysis of acoustic dynamic mechanism:

[0087] UV-vis DRS analysis: The UV-visible diffuse reflectance spectra (UV-Vis DRS) of NTO, BOS, NTO(Bi / N) and BOS@NTO(Bi / N) were measured by UV-visible spectrophotometer in the range of 200-800 nm using an integrating sphere. 4 Used as reflectance standard material.

[0088] XPS-VB analysis: The valence band potentials of NTO, BOS and NTO(Bi / N) were analyzed by collecting XPS-VB spectra.

[0089] The results are as follows Figure 4 As shown, Figure 4 Figure 1 is a schematic diagram of the Tauc curves and XPS-VB spectra of NTO, NTO (Bi / N) and BOS. Among them, a is a schematic diagram of the Tauc curve of NTO, b is a schematic diagram of the Tauc curve of NTO (Bi / N), c is a schematic diagram of the Tauc curve of BOS, d is a schematic diagram of the XPS-VB spectrum of NTO, e is a schematic diagram of the XPS-VB spectrum of NTO (Bi / N), and f is a schematic diagram of the XPS-VB spectrum of BOS.

[0090] The energy level structure test results show that the band gap of NTO is 3.96eV ( Figure 4 (shown in a), the valence band potential is 3.05 eV ( Figure 4 As shown in (d), the conduction band potential is -0.91 eV. Compared with NTO, the bandgap width of NTO (Bi / N) is reduced to 3.36 eV ( Figure 4 (shown in b), the valence band potential is 2.53 eV ( Figure 4 The conduction band potential is -0.83 eV. The bandgap width of BOS is 0.74 eV ( Figure 4 c), the valence band potential is 0.20 eV ( Figure 4 As shown in f), we can see that the conduction band potential is -0.64eV.

[0091] Electrochemical performance analysis: Electrochemical impedance spectroscopy (EIS) of the sample powder was tested by an electrochemical workstation; and US (1.5 W / cm 2 )Transient ultrasonic response current (it) curve of the sample excited by ultrasound.

[0092] The results are as follows Figure 5 As shown, Figure 5 Figure 1 is a schematic diagram of the electrochemical impedance spectra of NTO, NTO(Bi / N), BOS and BOS@NTO(Bi / N) and the it curves under ultrasonic irradiation. Figure 1 is a schematic diagram of the electrochemical impedance spectra of NTO, NTO(Bi / N), BOS and BOS@NTO(Bi / N), and Figure 1 is a schematic diagram of the it curves of NTO, NTO(Bi / N), BOS and BOS@NTO(Bi / N) under ultrasonic irradiation. Figure 5As shown in Figure a, the arc diameters of BOS@NTO(Bi / N) and NTO(Bi / N) are significantly smaller than that of NTO, and the arc diameter of BOS@NTO(Bi / N) is further reduced compared with NTO(Bi / N). This shows that doping reduces the charge transfer resistance of NTO(Bi / N) and promotes the separation and migration of electrons and holes; BOS promotes the transmission of electrons at the BOS@NTO(Bi / N) interface, which further enhances the separation and migration of electrons and holes in BOS@NTO(Bi / N). The sample it curve is shown in Figure 2. Figure 5 As shown in (b), compared with NTO, NTO(Bi / N) generates a stronger current, while the current intensity generated by BOS@NTO(Bi / N) is further improved than that of NTO(Bi / N), which also shows that BOS@NTO(Bi / N) has the best electron-hole pair separation efficiency.

[0093] PFM analysis: The piezoelectric properties of BOS@NTO(Bi / N) were analyzed by piezoresponse force microscopy (PFM, Bruker, USA).

[0094] The results are as follows Figure 6 As shown, Figure 6 (a) Amplitude image, (b) Phase image, (c) Amplitude butterfly loop and (d) Schematic diagram of hysteresis loop of BOS@NTO(Bi / N). Piezoelectric response amplitude of BOS@NTO(Bi / N) Figure 6 (shown in a) and phase ( Figure 6 The image shown in (b) shows obvious light and dark contrast; when the electric field is applied locally through the PFM tip, the amplitude ( Figure 6 c) and phase ( Figure 6 Hysteresis loops were observed in the signal channel (shown in (d), and when a reverse voltage was applied, a phase reversal of ~180° occurred, indicating that BOS@NTO(Bi / N) has good piezoelectric properties. The piezoelectric coefficient (d33) of BOS@NTO(Bi / N) was determined to be 69.20pm / V through a typical amplitude butterfly loop.

[0095] Figure 7 The schematic diagram of the mechanism of ROS generation by BOS@NTO(Bi / N) under US irradiation is shown in Figure 2. Figure 7 As shown in the figure, ion doping reduces the bandgap width of NTO(Bi / N). Under US irradiation, the piezoelectric effect of the heterojunction is excited, which enhances the separation of electrons and holes in the heterojunction. At the heterojunction interface, the electrons of NTO(Bi / N) flow to the BOS conduction band, which inhibits the recombination of electrons and holes. In this process, the holes in the valence band of NTO(Bi / N) continuously catalyze H 2 O generates ·OH, and the electrons in the BOS conduction band continuously catalyze O2 Generate O 2 - .

[0096] The preparation method of magnesium phosphate bone cement MPC / BOS@NTO (Bi / N) with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation comprises the following steps:

[0097] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of HA and MgO was 2:2:1, and hydroxyapatite (HA, Ca(PO 4 ) 3 (OH)) (5.5mmol, 2.76g) were mixed evenly, and the mass of hydroxyapatite (HA) accounted for 1.3% of CaHPO. 4 、NaH 2 PO 4 The mass percentage of the total mass of MgO is 10wt%. 5.53mL of deionized water is added to make the liquid-solid ratio 170μL / g, and the mixture is fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC.

[0098] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The mass percentage of the total mass of CaHPO is 10wt%. The obtained mixed powder is mixed with BOS@NTO(Bi / N) (7.59g) and the mass percentage of BOS@NTO(Bi / N) is 10wt%. 4 、NaH 2 PO 4The mass percentage of the total mass of MgO, hydroxyapatite and BOS@NTO(Bi / N) was 20wt%, 6.64mL of deionized water was added to make the liquid-solid ratio 170μL / g, and the mixture was fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample was placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC / BOS@NTO(Bi / N)-1(MBN-1).

[0099] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The obtained mixed powder was evenly mixed with BOS@NTO(Bi / N) (20.24 g), and BOS@NTO(Bi / N) accounted for 10 wt% of the total mass of CaHPO. 4 、NaH 2 PO 4 The mass percentage of the total mass of MgO, hydroxyapatite and BOS@NTO(Bi / N) is 40wt%, 7.75mL of deionized water is added to make the liquid-solid ratio 170μL / g, and the mixture is fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC / BOS@NTO(Bi / N)-2(MBN-2).

[0100] The sample groups are shown in Table 3:

[0101] Table 3. MPC / BOS@NTO (Bi / N) sample grouping

[0102] BOS@NTO(Bi / N) mass ratio Sample Abbreviation 0wt% MPC 20wt% MBN-1 40wt% MBN-2

[0103] Acoustic dynamic performance test of samples:

[0104] Rh B was used to detect the acoustic dynamic performance of the samples (·O 2 -and ·OH), and methylene blue (MB) and 1,3-diphenylisobenzofuran (DPBF) indicators were used to detect ·OH and ·O 2 - The sample was placed in 5 ml of indicator solution, US (1.5 W / cm 2 The supernatant was taken and the absorption spectrum was measured by UV-visible spectrophotometer. The concentrations of DPBF, MB and Rh B used were 5, 5 and 10 mg / L, respectively.

[0105] The results are as follows Figure 8 As shown, Figure 8 Figure 1 is a schematic diagram of the acoustic dynamic performance test results of the samples. a is a schematic diagram of the ROS generation ability of the samples evaluated by RhB degradation under US irradiation, b is a schematic diagram of the relationship between the ROS generation ability of MBN-2 and the US irradiation time, and c is a schematic diagram of the generation of ·OH and ·O by the composite material evaluated by MB. 2 - Schematic diagram of the ability results of the composite material to generate ·OH and ·O using DPBF. 2 - Schematic diagram of the results of the ability. In view of the excellent sonodynamic performance of BOS@NTO(Bi / N), magnesium phosphate bone cements MBN-1 and MBN-2 were prepared by blending BOS@NTO(Bi / N) with MPC, and the sonodynamic performance of MBN-1 and MBN-2 was tested. Figure 8 As shown in Figure a, compared with MPC, MBN-1 and MBN-2 have significantly improved their ability to generate ROS to degrade Rh B, and MBN-2 has the best sonodynamic performance. Figure 8 c) and O 2 - ( Figure 8 The test results of the influence of different US powers on the acoustic dynamic performance of MBN-2 are shown in Figure d. Figure 8 As shown in middle b, the ability of MBN-2 to generate ROS increased with the increase of US power.

[0106] Piezoelectric performance testing of samples: Use an oscilloscope to test the piezoelectric response voltage of the composite material, and use a current amplifier in parallel to test the piezoelectric response current, and use US to provide mechanical stress.

[0107] The results are as follows Fig. 9 As shown, Fig. 9It is a schematic diagram of the piezoelectric performance test results of the sample. Among them, a is a schematic diagram of the piezoelectric response voltage results of the sample, and b is a schematic diagram of the piezoelectric response current results of the sample. It can be seen from the figure that MPC only has a noise signal value and no piezoelectric response behavior is observed, while BOS@NTO(Bi / N) gives MBN-1 and MBN-2 obvious piezoelectric response, and it increases with the increase of heterojunction content. Among them, MBN-1 has an open circuit voltage of 0.31V and a short circuit current of 161μA; MBN-2 has an open circuit voltage of 0.64V and a short circuit current of 305μA.

[0108] Antibacterial experiment of samples: Staphylococcus aureus (S. aureus, ATCC 29213) and Escherichia coli (E. coli, ATCC 25922) were used to determine the in vitro antibacterial effect of the samples.

[0109] Sample groups: (1) MPC group, (2) MBN-2 group, (3) MPC+US group, and (4) MBN-2+US group.

[0110] MPC group: MPC samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS three times, and then placed in a 24-well cell culture plate for later use. 6 CFU·mL -1 , 1000 μL) was mixed with the MPC sample.

[0111] MBN-2 group: MBN-2 samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS for 3 times, and then placed in a 24-well cell culture plate for later use. 6 CFU·mL -1 , 1000 μL) was mixed with the MBN-2 sample.

[0112] MPC+US group: MPC samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS three times, and then placed in a 24-well cell culture plate for later use. Fresh bacterial suspension (1×10 6 CFU·mL -1 , 1000 μL) was mixed with the MPC sample. An ultrasonic device (1.5 W / cm 2 , 1 MHz) for 15 min.

[0113] MBN-2+US group: MBN-2 samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS three times, and then placed in a 24-well cell culture plate for later use. 6 CFU·mL -1 , 1000 μL) was mixed with the MBN-2 sample. An ultrasonic device (1.5 W / cm 2 , 1 MHz) for 15 min.

[0114] All samples were placed in a shaking incubator at 37°C for 6 h. Escherichia coli and Staphylococcus aureus were separated from the sample surface by ultrasound, and the bacterial suspension was collected. After diluting 10 times, 100 μL of the bacterial solution was evenly coated on LB agar by the ball rolling method, and the bacterial colonies formed after static culture at 37°C for 16 h were recorded and counted with a digital camera.

[0115] The results are as follows Fig.10 As shown, Fig.10 The colony image and bacterial survival rate of the antibacterial plate count are shown in Figure 1, where a is a colony image diagram and b is a bacterial survival rate diagram. *p<0.05, vs. MPC. The antibacterial plate count results show that, like MPC, MBN-2 has no significant anti-S. aureus effect, but under US (1.50W / cm 2 , 1MHz, 15min) treatment, MBN-2+US group had significant anti-S. aureus and E. coli effects compared with MPC+US group ( Fig.10 The survival rates of S. aureus and E. coli were 9.11±0.6% and 6.55±0.50%, respectively ( Fig.10 As shown in (b), the bar graph from left to right is MPC, MBN-2, MPC+US, MBN-2+US).

[0116] Cytotoxicity: The cell counting kit (CCK-8) was used to evaluate the effect of MBN-2 on cell viability under US irradiation. Rat bone marrow mesenchymal stem cells (rBMSCs) were cultured on the surface of the material and placed in a 24-well plate. Different powers of US (0, 0.1, 0.3, 0.5, 0.7, 0.9 W / cm 2 , 1MHz) irradiated the sample for 20s, and after treatment, CCK-8 solution (500μL) was added. Incubation continued for 2h, and the absorbance of the solution (100μL) was measured at a wavelength of 450nm by an enzyme reader.

[0117] Cell proliferation:

[0118] Sample groups: (1) MPC group, (2) MBN-2 group, (3) MPC+US group, and (4) MBN-2+US group.

[0119] MPC group: MPC samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS three times, and then placed in a 24-well cell culture plate for later use. 6 cells·mL -1 , 1000 μL) was mixed with the MPC sample.

[0120] MBN-2 group: MBN-2 samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS for 3 times, and then placed in a 24-well cell culture plate for later use. 6 cells·mL -1 , 1000 μL) was mixed with the MBN-2 sample.

[0121] MPC+US group: MPC samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS three times, and then placed in a 24-well cell culture plate for later use. 6 cells·mL -1 , 1000 μL) was mixed with the MPC sample. An ultrasonic device was placed at the bottom of the well plate and low-intensity pulsed ultrasound (0.5 W / cm 2 , 1MHz) irradiated the sample 3 times, each time for 20s.

[0122] MBN-2+US group: MBN-2 samples (20 mg) were sterilized by soaking in 75% ethanol for 30 min, washed with PBS for 3 times, and then placed in a 24-well cell culture plate for later use. 6 cells·mL -1 , 1000 μL) was mixed with the MBN-2 sample. An ultrasonic device was placed at the bottom of the well plate and low-intensity pulsed ultrasound (0.5 W / cm 2 , 1MHz) irradiated the sample 3 times, each time for 20s.

[0123] The cell counting kit (CCK-8, Bio-Sky, China) was used to evaluate the effect of MBN-2 on cell viability under US irradiation. Rat bone marrow mesenchymal stem cells (rBMSCs) were cultured on the surface of the material and placed in a 24-well plate. The irradiation was performed three times with an interval of 8 h using different powers of US (0, 0.1, 0.3, 0.5, 0.7, 0.9 W / cm 2MBN-2 was irradiated with 1 MHz (100 μL) for 20 s, and CCK-8 solution (500 μL) was added after treatment. The incubation was continued for 2 h, and the absorbance of the solution (100 μL) was measured at 450 nm using an ELISA reader.

[0124] The results are as follows Fig.11 As shown, Fig.11 Figure 1 is a schematic diagram of the cytotoxicity and cell proliferation results of the samples, where a is a schematic diagram of the cytotoxicity results of MBN-2 at different US powers, *p<0.05, vs. Control; b is a schematic diagram of the cell proliferation of rBMSCs after 1, 3 and 7 days of culture (*p<0.05, vs. MPC; #p<0.05, vs. MBN-2) (the bar graphs from left to right are MPC, MBN-2, MPC+US, MBN-2+US). Fig.11 As shown in a, compared with the control group (US power was 0 W / cm 2 , i.e. MPC group and MBN-2 group), when US power ≤ 0.5 W / cm 2 MBN-2 showed no cytotoxicity when the ultrasound intensity was ≥0.7 W / cm 2 Based on this, 0.5W / cm 2 The US power was used to investigate the ability of the sample to stimulate osteoblast proliferation by piezoelectric effect. Fig.11 As shown in middle b, after 7 days of co-culture with the sample, MBN-2 group promoted the proliferation of rBMSCs compared with MPC group, while 0.5W / cm 2 After US treatment, there was no significant change in cell proliferation in the MPC+US group. However, ultrasound can stimulate the piezoelectric effect of MBN-2, further improving the ability of MBN-2 to promote cell proliferation. The OD values ​​of the MPC group at 1, 3, and 7 days were 0.43, 0.61, and 0.85, respectively; the OD values ​​of the MBN-2 group at 1, 3, and 7 days were 0.31, 0.74, and 1.12, respectively; the OD values ​​of the MPC+US group at 1, 3, and 7 days were 0.42, 0.60, and 0.86, respectively; the OD values ​​of the MBN-2+US group at 1, 3, and 7 days were 0.66, 0.95, and 1.58, respectively; at 7 days, the cell proliferation of the MBN-2+US group was 46.2% higher than that of the MPC group.

[0125] The present invention prepares a heterojunction of NTO (Bi / N) and BOS (BOS@NTO (Bi / N)). Due to ion doping, the band gap of NTO (Bi / N) is reduced and the piezoelectric performance of NTO (Bi / N) is improved, which is conducive to the generation of electron-hole pairs in the heterojunction under US irradiation. At the same time, BOS inhibits the recombination of electron and hole pairs, thereby enhancing the acoustic dynamic performance of the heterojunction. Magnesium phosphate bone cement MPC / BOS@NTO (Bi / N)-2 (MBN-2) is prepared. Compared with MPC, BOS@NTO (Bi / N) gives MBN-2 excellent piezoelectric properties. This is because ion doping causes lattice distortion and promotes the fluidity of domain walls. In addition, due to the excellent electron transmission ability of BOS, the bulk conductivity of MBN-2 is improved, and the two together lead to enhanced piezoelectric properties. Antibacterial experiments show that under US irradiation, MBN-2 produces ROS to kill bacteria (S. aureus and E. coli). Cell experiments showed that MBN-2 promoted osteoblast proliferation through its piezoelectric effect.

[0126] Example 2

[0127] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The total mass percentage of MgO is 10wt%. 6.19mL of deionized water is added to make the liquid-solid ratio 190μL / g, and the mixture is fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC.

[0128] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The obtained mixed powder was evenly mixed with BOS@NTO(Bi / N) (7.59 g), and BOS@NTO(Bi / N) accounted for 10 wt% of the total mass of CaHPO. 4 、NaH 2 PO 4 The mass percentage of the total mass of MgO, hydroxyapatite and BOS@NTO(Bi / N) was 20wt%, 8.16mL of deionized water was added to make the liquid-solid ratio 190μL / g, and the mixture was fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample was placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC / BOS@NTO(Bi / N)-3(MBN-3).

[0129] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The obtained mixed powder was evenly mixed with BOS@NTO(Bi / N) (20.24 g), and BOS@NTO(Bi / N) accounted for 10 wt% of the total mass of CaHPO. 4 、NaH 2 PO 4 The mass percentage of the total mass of MgO, hydroxyapatite and BOS@NTO(Bi / N) is 40wt%, 9.53mL of deionized water is added to make the liquid-solid ratio 190μL / g, and the mixture is fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC / BOS@NTO(Bi / N)-4(MBN-4).

[0130] Table 4. MPC / BOS@NTO (Bi / N) sample grouping

[0131]

[0132] Example 3

[0133] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The total mass percentage of magnesium phosphate cement (MPC) was 10 wt %. 7.52 mL of deionized water was added to make the liquid-solid ratio 210 μL / g, and the mixture was fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10 mm), and the mixture was taken out after molding. The sample was placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 72 h to obtain 5 g of magnesium phosphate cement (MPC).

[0134] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The obtained mixed powder was evenly mixed with BOS@NTO(Bi / N) (7.59 g), and BOS@NTO(Bi / N) accounted for 10 wt% of the total mass of CaHPO. 4 、NaH 2 PO 4The mass percentage of the total mass of MgO, hydroxyapatite and BOS@NTO(Bi / N) is 20wt%, 8.60mL of deionized water is added to make the liquid-solid ratio 210μL / g, and the mixture is fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC / BOS@NTO(Bi / N)-5(MBN-5).

[0135] CaHPO 4 (0.1 mol, 13.60 g), NaH 2 PO 4 (0.1 mol, 12.00 g) and MgO powder (0.05 mol, 2 g) were mixed, CaHPO 4 、NaH 2 PO 4 The molar ratio of CaHPO to MgO was 2:2:1, and hydroxyapatite (HA) (5.5 mmol, 2.76 g) was added and mixed evenly. The mass of hydroxyapatite (HA) accounted for 1.3% of the mass of CaHPO. 4 、NaH 2 PO 4 The obtained mixed powder was evenly mixed with BOS@NTO(Bi / N) (20.24 g), and BOS@NTO(Bi / N) accounted for 10 wt% of the total mass of CaHPO. 4 、NaH 2 PO 4 The mass percentage of the total mass of MgO, hydroxyapatite and BOS@NTO(Bi / N) is 40wt%, 10.53mL of deionized water is added to make the liquid-solid ratio 210μL / g, and the mixture is fully mixed and filled into a polytetrafluoroethylene mold (Φ10×10mm), and taken out after molding. The sample is placed in an incubator at a temperature of 37°C and 100% humidity for curing for 72h to obtain 5g of magnesium phosphate bone cement MPC / BOS@NTO(Bi / N)-6(MBN-6).

[0136] Table 5. MPC / BOS@NTO (Bi / N) sample grouping

[0137]

[0138] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation, characterized in that: The invention is made of CaHPO4, NaH2PO4, MgO powder, hydroxyapatite and a heterojunction containing BOS. The molar ratio of CaHPO4, NaH2PO4 and MgO is 1-4:1-4:1, the mass of hydroxyapatite accounts for 5-20wt% of the total mass of CaHPO4, NaH2PO4 and MgO, and the mass of the heterojunction containing BOS accounts for 5-50wt% of the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and the heterojunction containing BOS.

2. The magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to claim 1, characterized in that: The BOS-containing heterojunction is made of Bi / N co-doped NaTaO3 nanomaterials, bismuth nitrate Bi(NO3)3, N2H4·H2O, SeO2 and sodium hydroxide in a mass ratio of 1-100:1-50:1:0.1-10:1-500.

3. The magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to claim 2, characterized in that: The Bi / N co-doped NaTaO3 nano material is made of tantalum pentoxide Ta2O5, Bi(NO3)3, ammonia water and sodium hydroxide in a molar ratio of 1:0.005-0.04:1-5:1-100.

4. A method for preparing the magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to any one of claims 1 to 3, characterized in that: The following steps are involved: The powders of CaHPO4, NaH2PO4 and MgO are mixed in a molar ratio of 1 to 4:1 to 4:1, hydroxyapatite is added and mixed evenly, wherein the mass of hydroxyapatite accounts for 5 to 20 wt% of the total mass of CaHPO4, NaH2PO4 and MgO, the obtained mixed powder is mixed evenly with a heterojunction containing BOS, wherein the mass of the heterojunction containing BOS accounts for 5 to 50 wt% of the total mass of CaHPO4, NaH2PO4, MgO, hydroxyapatite and the heterojunction containing BOS, deionized water is added so that the liquid-solid ratio is 170 to 210 μL / g, the mixture is fully blended and filled into a mold, formed, and cured to obtain the magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation.

5. The method for preparing magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to claim 4, characterized in that: The curing conditions are as follows: the sample is placed in an incubator at a temperature of 37° C. and a humidity of 100% for curing for 1 to 72 hours.

6. The method for preparing magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to claim 4, characterized in that: The method for preparing the heterojunction containing BOS comprises the following steps: Dissolve 20-50 wt% N2H4·H2O and SeO2 in a 5-15 M NaOH aqueous solution, with a volume ratio of N2H4·H2O to the NaOH aqueous solution being 0.1-1:1, and stir continuously for 20-60 min to obtain solution A; Disperse the Bi / N co-doped NaTaO3 nanomaterials into a 0.1-1M NaOH aqueous solution containing Bi(NO3)3, and stir for 20-60 min to obtain a solution B; The mass ratio of Bi / N co-doped NaTaO3 nanomaterial, bismuth nitrate Bi(NO3)3, N2H4·H2O, SeO2, and sodium hydroxide is 1-100:1-50:1:0.1-10:1-50; Solution A is added dropwise to solution B and stirred for 0.5 to 2 hours, the volume ratio of solution A to solution B is 1.1 to 1.5:1, and a hydrothermal reaction is carried out at a temperature of 150 to 300° C. for 0.5 to 24 hours. After the reaction, the product is washed and dried to obtain the heterojunction containing BOS.

7. The method for preparing magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to claim 6, characterized in that: The preparation method of the Bi / N co-doped NaTaO3 nanomaterial comprises the following steps: Ta2O5 is dispersed in a NaOH solution with a concentration of 0.5 to 3M, with a molar ratio of Ta2O5 to NaOH of 1:1 to 100; Bi(NO3)3 and ammonia water are added to the above solution as Bi source and N source, with a molar ratio of Ta2O5, Bi(NO3)3 and ammonia water of 1:0.005 to 0.04:1 to 5; the mixture is stirred for 0.5 to 2h in a sealed state, reacted at a temperature of 140 to 200°C for 0.5 to 24h, washed with deionized water, dried, and annealed to obtain the Bi / N co-doped NaTaO3 nanomaterial.

8. The method for preparing magnesium phosphate bone cement with sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation according to claim 7, characterized in that: The drying conditions are as follows: drying at a temperature of 50 to 80° C. for 0.5 to 24 hours; The annealing conditions are: annealing at a temperature of 350 to 500° C. for 0.5 to 2 hours.

9. Use of the magnesium phosphate bone cement having sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation as claimed in any one of claims 1 to 3 in the preparation of bone repair scaffolds.

10. Use of the magnesium phosphate bone cement having sonodynamic antibacterial / piezoelectric effect to stimulate cell proliferation as claimed in any one of claims 1 to 3 in the preparation of bone repair materials or bone transplant materials.